Sphenoid Ridge Lymphoplasmacyte-rich Meningioma - Joon-Khim Loh; Shiuh-Lin Hwang; Kun-Bow Tsai; Aij-Lie Kwan; Shen-Long Howng (Journal of the Formosan Medical Association, 2006)
There are numerous histologic variants of meningioma. Among the more uncommon are intracranial masses composed of meningiomatous and plasma cell-lymphocytic elements. We report a 22-year-old woman with lymphoplasmacyte-rich meningioma who initially presented with dizziness and progressive headache. Neuroradiologic images revealed typical meningiomas of the sphenoid ridge with extensive perifocal edema. Complete macroscopic removal of the tumor was performed. Histologic examination revealed a meningioma with massive infiltrates of plasma cells and lymphocytes. Brain computed tomography on the 6th postoperative day revealed total removal of the tumor with marked reduction of brain edema. Complete resolution of symptoms occurred with no evidence of tumor recurrence during 2 years of follow-up.